2015
DOI: 10.1111/ijd.12644
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris: a clinical study of 44 cases over a 20‐year period

Abstract: Poor prognosis factors include the severe mucocutaneous type of PV, especially in female patients, and multiple mucosal involvements in the oral cavity and other mucosal sites. Female patients were younger than male patients and were more often observed to have severe mucocutaneous PV and to have a higher median period of remission survival than male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 19 publications
8
29
6
Order By: Relevance
“…For pemphigus, relapses were observed in all our patients with a mean delay of 8.75 months and these relapses could be late (up to 34 months). Complete remission was long to obtain, as for adults . In our series, only 7 patients were in complete remission, within a mean delay of 49.1 months (17–96 months).…”
Section: Discussionmentioning
confidence: 48%
“…For pemphigus, relapses were observed in all our patients with a mean delay of 8.75 months and these relapses could be late (up to 34 months). Complete remission was long to obtain, as for adults . In our series, only 7 patients were in complete remission, within a mean delay of 49.1 months (17–96 months).…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, in the same study, anti-Dsg3 IgG4 autoantibody levels were significantly higher in patients who carried one or both of the disease-associated HLA alleles (DRB1*04:02 and DQB1*05:03) than in carriers of other HLA alleles. 16 Other authors have documented poor prognoses in PV patients aged ≤40 years with initial mucosal involvement. Analysis of the DRB1* and DQB1* alleles with additional clinical parameters highlights the association of DRB1*04:02 alleles with severe PV (P = 0.031) and with the mucocutaneous type of PV (P = 0.024); further, the frequency of the alleles is greater than in carriers of other HLA alleles.…”
Section: Discussionmentioning
confidence: 97%
“…6 Our previous study confirmed high allele frequencies of DRB1 and DQB1 in PV patients in Slovakia. 16 Furthermore, the presence of the DQB1*03:02 allele has been shown to be increased significantly in PV patients. 7 Because the course of PV is frequently unpredictable, the identification of parameters that may predict the course and prognosis of the disease are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Pemphigus vulgaris (PV) is a chronic, autoimmune intraepithelial blistering disease that affects any mucosal or cutaneous surface lined by squamous epithelium . Its incidence is 0.1 to 0.5 per 100,000 patients per year, and it commonly affects 40‐ to 60‐year‐old women of Jewish or Mediterranean descent, despite being described in all ages and every ethnic group …”
Section: Introductionmentioning
confidence: 99%
“…Before the introduction of oral corticosteroids in the 1950s, PV had a 90% mortality rate . Even today, a 6% to 10% mortality rate is typically reported for PV patients . A better prognosis is usually associated with early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%